Survivre, renverser, réparer : personnages féminins et animaux à la fin de l’Androcène - Jodie Lou Bessonnet (Glad!)
Knowing the “critical power” (Engélibert, 2019) held by apocalyptic fictions and choosing to go against the virilist representations that infuse the postapocalyptic imagination (Ruault et al., 2021), this study analyses three contemporary fictions shifting towards female and animal characters : MaddAddam by Margaret Atwood (2004, 2010, 2013), Sirene by Laura Pugno (2007) and Les Métamorphoses by Camille Brunel (2020). These novels look at the Anthropocene not only through the environmental approach but also through the prism of an animal ethic, considering the crossing between sexism and specism that Carol Adams identified as the “sexual politics of meat” (2010 [1990]). The apocalyptic novel allows however to reverse the power relationships, through a defensive violence first, but then opening to a potential reparation as the disaster questions the possibility of a feminist and anti-speciesist utopia.